PARACERVICAL BLOCK CARDIOTOCOGRAPHIC OF PREGNANT AND CONTROL IN LABOR - Haro Sánchez, Ángel (2015)
Paracervical block is to interrupt the hypogastric nerve ganglia Lee-Frankenhauser in the first stage of labor influence, this is during the expansion Dase.